2009
DOI: 10.1247/csf.09006
|View full text |Cite
|
Sign up to set email alerts
|

Increased Motility and Invasiveness in Tumor Cells That Survive 10 Gy Irradiation

Abstract: ABSTRACT. Radiotherapy is an important noninvasive treatment for many types of cancer. However, it has been reported that the proliferative, invasive, and metastatic capacities of tumor cells can be increased in the repopulated tumors that survive radiotherapy. We have previously established a radiation-surviving cell model for the human non-small cell lung cancer cell line H1299 by harvesting relic cells 14 days after irradiation (IR cells). Here, we report that cell invasion, cell migration, and cell adhesio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
33
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 30 publications
(36 citation statements)
references
References 20 publications
3
33
0
Order By: Relevance
“…Mouse fibrosarcoma QRsP cells exhibit an enhanced invasive activity after survival through 10 Gy irradiation [14]. Moreover, in human non-small lung cancer H1299 cells, invasiveness is enhanced after 10 Gy irradiation [3]. Increase in invasive activity after irradiation might be a common phenomenon in cancer cells making it difficult to use radiotherapy as a single modality treatment for the complete cure of many malignant cancers.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mouse fibrosarcoma QRsP cells exhibit an enhanced invasive activity after survival through 10 Gy irradiation [14]. Moreover, in human non-small lung cancer H1299 cells, invasiveness is enhanced after 10 Gy irradiation [3]. Increase in invasive activity after irradiation might be a common phenomenon in cancer cells making it difficult to use radiotherapy as a single modality treatment for the complete cure of many malignant cancers.…”
Section: Discussionmentioning
confidence: 99%
“…However, it has been reported that local tumor irradiation can lead to enhancement of metastases [1]. Recent studies indicate that tumors surviving irradiation acquire high metastatic ability in vivo [2], and the irradiation-tolerant cancer cells enhance cellular physiological activities, such as invasion, migration, and adhesion in vitro [3]. These results suggest that irradiation of tumors could induce malignant transformation and result in poor prognosis, although the detailed mechanism is not well understood.…”
Section: Introductionmentioning
confidence: 99%
“…In previous studies, conventional cell lysis methods, which do not involve TCA fixation and collagenase treatment, were often used for WB (Engler et al 2006;Tsutsumi et al 2009;Wu et al 2009). In these studies, the cells were cultured on polyacrylamide gels, plastic plates, or dishes.…”
Section: Resultsmentioning
confidence: 99%
“…Thus, by means of the collagenase treatment, we were able to dissolve the collagen gel and remove it from cell lysates. In previous studies, researchers often lysed the cells without TCA and collagenase treatment for WB (Wang et al 2003;Engler et al 2006;Tsutsumi et al 2009;Wu et al 2009). We refer to this approach as ''the conventional method'' in this study.…”
Section: Introductionmentioning
confidence: 99%
“…After surgical removal of primary breast tumors, malignant cells may still remain and radiotherapy is an efficient modality to reduce the risk of local recurrence. However, proliferative, invasive, and metastatic capacities can be increased in the surviving tumor cells of irradiated breast and other neoplasias (Baluna et al, 2006;Tsukamoto et al, 2007;Tsutsumi et al, 2009). To improve the efficacy of radiotherapy, this phenomenon must be further studied to elaborate therapeutic modalities to prevent radiation enhancement of cancer cell invasion.…”
Section: Introductionmentioning
confidence: 99%